The Concept of Technique Systems in the Notion of Smart Buildings Architecture (Journal of Engineering, 2008)
The magical brilliance between the information abilities and the abilities ofcontrolling the environment and consuming power, which distinguishes the smartbuildings. It becomes unavoidable and common things in different fields ofarchitecture like governmental, public, service and productive. Even on the level ofplanning the city center and urban.That might be attributed in first rank to the vital role of the computer in allaspects of life until the conditioned buildings that are able to fulfill necessary needs ofthe consumer. It also becomes necessary to provide the conditions of comfort,kindness and entertainment, as regard smart buildings depends in basically in designand the work of the internal, utilitarian and service structure on service systems. Theyare developed technological techniques that depend in their work on highdevelopment and keeping pace with the changes and developments of the informationrevolution in order to give the fruit of perfect and interactive buildings that offers tothe resident comfort environment in order to able to perform their tasks highly.